PROSES PEMBUATAN SILASE PENYEDIAAN HIJAUAN PAKAN TERNAK BERKUALITAS DAN KONTINU SEPANJANG TAHUN GUNA MENINGKATKAN PRODUKTIVITAS TERNAK RUMINANSIA DI NABIRE PAPUA - Mery C. Simanjuntak; Trijaya Gane Putra; Wardhana Wahyu Dharsono (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2023)
Seeing the livestock population in the Nabire district of Papua, it is necessary to prepare the feed properly. Lack of feed during the dry season can be overcome by utilizing the abundance of feed during the rainy season. The strategy is to increase the shelf life of the forage that will be prepared as forage for use in the dry season by preserving the forage. One type of forage preservation is "silage". With the direct practice method of making silage under the guidance of a facilitator from a Lecturer in the Animal Husbandry Study Program, Faculty of Agriculture and Animal Husbandry, Satya Wiyata Mandala University. Activities are divided into 3 namely Preparation, Work Practice and Closing. From the results of the practice by the participants, it was found that physically (organoleptic) the quality of the silage produced was of relatively good quality because of the smell or aroma, texture, presence of mold and color of the silage as follows: 1. The smell or aroma of the silage smells sweet and sour and is free of bad smell . 2. The texture is crumbly/clear, not mushy, not lumpy and not slimy. 3. Silage is not moldy. 3. The color is greenish (bright) and looks cooked like boiling